Pengaruh Program Pemutihan PKB, Sistem E-Samsat, Sosialisasi Perpajakan dan Kesadaran Wajib Pajak terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor dengan Kualitas Pelayanan Sebagai Variabel Moderasi di Kabupaten Sidoarjo - Haryadi, Hesty; Ernandi , Herman (Indonesian Journal Publisher, 2024)
This study aims to see whether the service quality variable is able to moderate the relationship between the PKB whitening program, the e-samsat system, tax socialization and taxpayer awareness of motor vehicle taxpayer compliance in Sidoarjo Regency. The data used is primary data in the form of questionnaire data. Determination of the sample using incidental sampling, and the data was tested using the SmartPLS version 3.0 program. The result showed that the PKB whitening program, e-samsat system and taxpayer awareness had an effect on motor vehicle taxpayer compliance which was moderated by service quality in Sidoarjo Regency. However, the socialization of taxation does not effect the compliance of motor vehicle taxpayers which is moderated by the quality of service in Sidoarjo Regency.